PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR DESA DI DESA SIMPANG ARJA KECAMATAN RANTAU BADAUH KABUPATEN BARITO KUALA - ade - hermawan; Bakhtiar Bakhtiar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The results showed that the implementation of infrastructure development in Simpang Arja Village, Rantau Badauh District, Barito Kuala Regency was quite good with the realization of the construction of farm roads and village markets. Constraints in development, limited funds, lack of public concern for development in the village and the problem of erratic weather hampered development work.